Republic of Mozambique : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Mozambique. (IMF Staff Country Reports; Country Report, 2019)
Mozambique's economic situation had been improving until Tropical Cyclone Idai and Kenneth hit the country in March and April, respectively. Economic growth was recovering gradually and becoming broader based, and inflation reached low single digits. Economic activity is expected to decelerate sharply in 2019 due to the supply shock to productive capacity, but it should rebound to pre-cyclone levels by 2020. In April, the IMF Executive Board approved USD 118 million in emergency assistance under the Rapid Credit Facility (RCF). The authorities are committed to macroeconomic stability while fostering inclusive growth and addressing governance challenges.